Tratamentos de efluente de processo de polpa quimiotermomecânica CTMP - Grötzner, Mariana de Bittencourt (2014)
Pulp and paper sector contributes significantly to Brazilian economy, accordingly to the crescent grow in production of pulp and paper in the last years. Effluent generated in mills of this sector is commonly formed by organic compounds originated from lignin molecules degradation. In general, contaminants are measured through color, chemical oxygen demand (COD), biochemical oxygen demand (BOD), total organic carbon (TOC), lignin compounds, turbidity, solids and phenolic compounds contents. The aim of this study was to run a technically feasible treatment for an effluent from CTMP (chemiothermalmechanical pulping) plant. According to the literature, different methods can be applied for this kind of effluent. Physical-chemical treatment of coagulation-flocculation-sedimentation was performed and the conditions of pH, coagulant type and concentration and settling time were optimized. Coagulant concentration and pH curves verified the best treatment condition, which were: pH 3.0, aluminum sulphate as coagulant, concentration of coagulant at 750 mg.L-1 and settling time of 60 minutes. The removal efficiencies obtained for these condition were 20, 40 and 50% for COD, color and turbidity, respectively. The TOC removal was 78% and toxicity was not changed due to the treatment. For the optimized condition of the treatment, it was testes a high molar mass cationic flocculant, which demonstrated improvements in the removal efficiencies in 10% (average). The effluent treated using the most efficient condition of the physical-chemical treatment passed through a oxidative process – Fenton. In this sense, it was obtained removal of COD and TOC of 51.6 and 78.9%, respectively. Finally, the combined methods lead to a total removal of 74% for turbidity, 53% for color, 61% for COD and 95% for TOC.